Practical security against differential cryptanalysis of extended feistel network - Ibrahim, Subariah (2007)
Immunity against differential cryptanalysis is an important measure in designing symmetric ciphers. Practical security is a measure to evaluate this immunity by estimating the minimum number of differential active s-boxes. A cipher with more s-boxes is said to have better immunity against differential cryptanalysis. In this paper, we evaluate the immunity of three types of Extended Feistel Network (EFN) with Substitution-Permutation (SP) round function and compare it with a balanced Feistel Network (FN). Weight-Based Representation (WBR) of sub-blocks is employed in estimating the minimum number of s-boxes of these cipher structures. The result shows that EFN Type-II and EFN Type-III have better immunity to differential cryptanalysis than a balanced FN. This is due to a difference cancellation that occurs more often in a balanced FN.